The Politics of Body in Bhisham Sahni's Madhavi: Rethinking the Mythical Performance - Lamichhane, Yog Raj (SCHOLARS: Journal of Arts & Humanities, 2021)
Madhavi, a blessed body with eternal virginity, is the central character of Bhisham Sahni's play Madhavi. This paper attempts to explore her boon of eternal virginity as a patriarchal scar inscribed by the society on her womb. How do her ultimate rejection of that scar and the final journey to actual eternity become the insightful performances to respond to the societal body politics? This is the major concern of the study. In this interpretation, mainly the concepts of Michel Foucault and Judith Butler regarding the body politics and the notions of Jennifer Parker-Starbuck, Roberta Mock, and Richard Schechner concerning the body and its performance are synthesized as a theoretical framework to analyze the textual evidence and to observe the performance of the politically conditioned, condemned and trivialized body of Madhavi. Finally, the study ascertains that the perpetually subordinated body gradually comprehends the society and insightfully performs liberty against the hegemonic power bloc. In the play, the proactive proposal of Madhavi to Vishwamitra for lovemaking and her ultimate disappearance into nature in search of actual eternity can be a leading evidence of the insightful performances towards liberty.